The Increased Sensitivity of Platelets to Prostacyclin in Marathon Runners - Dix, Clive J; Hassall, David G; Bruckdorfer, K Richard (Thrombosis and Haemostasis, 1984)
Platelet-rich plasma was obtained 24 hr after the race ended from athletes who ran in the London marathon. The platelets were only marginally less sensitive to adrenaline than were those of non-runners using conventional aggregation tests. However, the runners’ platelets were much more sensitive to inhibition by prostacyclin, a prostaglandin synthesized by endothelial cells. It appeared that this effect was due to a greater activity in the platelets of the membrane-bound adenylate cyclase enzyme which generates intracellular cyclic AMP. Cyclic AMP production is known to be stimulated by prostacyclin and to cause the inhibition of platelet aggregation. The results indicate another possible protective effect of exercise against cardiovascular disease which is independent of the known changes in lipoprotein concentrations previously observed in athletes.
Keywords: Marathon runners; Platelet aggregation; Prostacyclin; Lipoproteins